Sensitivity of SARS-CoV-2 RNA polymerase chain reaction using a clinical and radiological reference standard. Issue 6 (June 2021) - Stockdale, Alexander J; Fyles, Fred; Farrell, Catriona; Lewis, Joe; Barr, David; Haigh, Kathryn; Abouyannis, Michael; Hankinson, Beth; Penha, Diana; Fernando, Rashika; Wiles, Rebecca; Sharma, Sheetal; et al.
Highlights: Compared to a clinical and radiological standard, SARS-CoV-2 PCR sensitivity was 68%. Sensitivity declined after one week from patient-reported symptom onset. Test sensitivity was lower among current smokers compared to never/former smokers. Lower test sensitivity among smokers may explain lower observed disease incidence. Abstract: Objectives: Diagnostic tests for SARS-CoV-2 are important for epidemiology, clinical management, and infection control. Limitations of oro-nasopharyngeal real-time PCR sensitivity have been described based on comparisons of single tests with repeated sampling. We assessed SARS-CoV-2 PCR clinical sensitivity using a clinical and radiological reference standard. Methods: Between March-May 2020, 2060 patients underwent thoracic imaging and SARS-CoV-2 PCR testing. Imaging was independently double- or triple-reported (if discordance) by blinded radiologists according to radiological criteria for COVID-19. We excluded asymptomatic patients and those with alternative diagnoses that could explain imaging findings. Associations with PCR-positivity were assessed with binomial logistic regression. Results: 901 patients had possible/probable imaging features and clinical symptoms of COVID-19 and 429 patients met the clinical and radiological reference case definition. SARS-CoV-2 PCR sensitivity was 68% (95% confidence interval 64–73), was highest 7-8 days after symptom onset (78% (68–88)) and was lower among current smokers (adjusted odds ratio 0.23 (0.12–0.42) p  < 0.001). Conclusions: In patients with clinical and imaging features of COVID-19, PCR test sensitivity was 68%, and was lower among smokers; a finding that could explain observations of lower disease incidence and that warrants further validation. PCR tests should be interpreted considering imaging, symptom duration and smoking status.